Cell-Mediated Immune Responses to COVID-19 Infection - Guihot, Amélie; Litvinova, Elena; Autran, Brigitte; Debré, Patrice; Vieillard, Vincent (Frontiers in Immunology, 2020)
An unprecedented outbreak of pneumonia caused by a novel coronavirus (CoV), subsequently termed COVID-19 by the World Health Organization, emerged in Wuhan City (China) in December 2019. Despite rigorous containment and quarantine efforts, the incidence of COVID-19 continues to expand, causing explosive outbreaks in more than 160 countries with waves of morbidity and fatality, leading to significant public health problems. In the past 20 years, two additional epidemics caused by CoVs have occurred: severe acute respiratory syndrome-CoV, which has caused a large-scale epidemic in China and 24 other countries; and respiratory syndrome-CoV of the Middle East in Saudi Arabia, which continues to cause sporadic cases. All of these viruses affect the lower respiratory tract and manifest as pneumonia in humans, but the novel SARS-Cov-2 appears to be more contagious and has spread more rapidly worldwide. This mini-review focuses on the cellular immune response to COVID-19 in human subjects, compared to other clinically relevant coronaviruses to evaluate its role in the control of infection and pathogenesis and accelerate the development of a preventive vaccine or immune therapies